KEKUATAN ALAT BUKTI PENYADAPAN DALAM PERKARA TINDAK PIDANA KORUPSI - Mohammad Fahmi Amrullah (Fakultas Hukum Universitas Islam Malang, 2020)
AbstractNowadays there is a lot of Corruption committed by state officials in Indonesia. Therefore the Corruption Eradication Commission (KPK) as an Independent Institution, has a tough task to investigate the perpetrators of Corruption in Indonesia. Of course the KPK in the trial requires strong evidence in revealing the special criminal offender, namely corruption. With this evidence, the Corruption Eradication Commission will be able to prove that the perpetrators are proven to have committed criminal acts of corruption. It is known that the Corruption Eradication Commission has just been revised, Act Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 Concerning the Commission Eradication of Corruption.Where there are changes to the procedures listed in the new law. Referring to how the KPK can conduct wiretapping and obtain official permission to conduct wiretapping of perpetrators who are indicated to have committed crimes of corruption.Keywords: Tapping, Corruption, Strength of Evidence.ABSTRAKSaat ini marak sekali terjadi Tindak Pidana Korupsi yang dilakukan oleh para pejabat negara di Indonesia. Maka dari itu Komisi Pemberantasan Korupsi (KPK) sebagai Lembaga Independen, memiliki tugas berat untuk mengusut pelaku Tindak Pidana Korupsi di Indonesia. Tentu pihak KPK dalam persidangan memerlukan alat bukti yang kuat dalam mengungkap pelaku pidana khusus yaitu korupsi. Dengan adanya alat bukti tersebut, KPK akan dapat membuktikan bahwa pihak pelaku terbukti melakukan tindak pidana korupsi Di ketahui bahwa Undang-undag KPK baru saja di revisi, Undang-undang Nomor 19 Tahun 2019 Tentang Perubahan Kedua Atas Undang-undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi.Dimana ada perubahan prosedur yang tertera di undang-undang baru tersebut. Mengacu pada bagaimana KPK dapat melakukan penyadapan dan mendapat izin resmi untuk melakukan penyadapan terhadap pelaku yang terindikasi melakukan kejahatan tindak pidana korupsi.Kata Kunci: Penyadapan, Tindak Pidana Korupsi, Kekuatan Alat Bukti.